Implementation of Road Traffic Observation with ETLE as a Form of Legal Development in the Digital Era - Loeky Kristanto; Wieke Dewi Suryandari; Hono Sejati (UNES Law Review, 2024)
Legal development in the digital era, the implementation of road traffic monitoring with ETLE (Electronic Traffic Law Enforcement) is a new thing in Indonesia. As an innovation, the electronic traffic monitoring system (ETLE) continues to experience continuous development and improvement. It is relevant because the development of ETLE is conducted within an existing legal framework related to traffic regulations, which will most likely interact with other legal aspects in the context of road traffic law enforcement. The research aims to examine the existence of ETLE in the context of the development of traffic law in Indonesia in the digital era, as well as the extent to which traffic law in force in Indonesia is appropriate in responding to the use of ETLE as a new tool in enforcing road traffic law. The method used is a normative juridical method by reviewing existing regulations and literature related to the application of ETLE and traffic law in Indonesia. The research results show that ETLE is a lineup with the direction of the development of Indonesian national law, especially in the context of the current digital era. Apart from that, traffic law in Indonesia also tends to be in line with the use of ETLE as a new tool in enforcing traffic law, although several legal aspects need special attention.